2022
DOI: 10.1073/pnas.2115316119
|View full text |Cite
|
Sign up to set email alerts
|

HTLV-1 activates YAP via NF-κB/p65 to promote oncogenesis

Abstract: Adult T-cell leukemia/lymphoma (ATL) is an aggressive malignancy caused by human T-cell leukemia virus type 1 (HTLV-1) infection. HTLV-1 exerts its oncogenic functions by interacting with signaling pathways involved in cell proliferation and transformation. Dysregulation of the Hippo/YAP pathway is associated with multiple cancers, including virus-induced malignancies. In the present study, we observe that expression of YAP, which is the key effector of Hippo signaling, is elevated in ATL cells by the action o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 52 publications
0
23
1
Order By: Relevance
“…36 Moreover, we found that YAP could interact with Tax. 36 Thus we speculate whether YAP may have other critical roles in promoting leukemogenesis through association with Tax protein.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…36 Moreover, we found that YAP could interact with Tax. 36 Thus we speculate whether YAP may have other critical roles in promoting leukemogenesis through association with Tax protein.…”
mentioning
confidence: 83%
“…36 NF-κB/p65-induced YAP activation was essential for maintaining the proliferation of ATL cells in vitro and in vivo. 36 Moreover, we found that YAP could interact with Tax. 36 Thus we speculate whether YAP may have other critical roles in promoting leukemogenesis through association with Tax protein.…”
mentioning
confidence: 97%
“…Tax and HBZ are currently acknowledged as two HTLV‐1 oncogenes with quite distinct mechanisms for oncogenesis. Tax is able to activate important cellular pathways including those responsible for T‐cell activation and expansion, 35 and is thereby considered a key player in HTLV‐1 persistence. Meanwhile, Tax appears to be a strong antigen that triggers cytotoxic T cell (CTL) response killing HTLV‐1 infected cells effectively.…”
Section: Tax and Hbzmentioning
confidence: 99%
“…Finally, the Hippo signal effector, YAP, known for its implication in the regulation of glutaminolysis, was found to be activated in ATL and its activation to be essential to maintain cellular proliferation of HTLV-1-infected cells. The activation was found to be induced via Tax protein through NF-κB [ 222 ].…”
Section: Metabolic Reprogramming In Oncovirusesmentioning
confidence: 99%